The International Study of Asthma and Allergies in Childhood (Isaac) Phase Three: A Global Synthesis - Mallol-Villablanca, E (2013)
This ISAAC Phase Three synthesis provides summarised information on the main findings of the study, regional tables and figures related to the prevalence and severity of current symptoms of asthma, rhinoconjunctivitis and eczema in the main regions of the world. The large number of surveyed children (?1,200,000), the large number of centres (233) and countries (98) that participated in ISAAC Phase Three makes this study the most comprehensive survey of these diseases ever undertaken. Globally, the prevalence for current asthma, rhinoconjunctivitis and eczema in the 13-14-year age group was 14.1%, 14.6% and 7.3%, respectively. In the 6-7-year age group the prevalence for current asthma, rhinoconjunctivitis and eczema was 11.7%, 8.5% and 7.9%, respectively. The study shows a wide variability in the prevalence and severity of asthma, rhinoconjunctivitis and eczema which occurs not just between regions and countries but between centres in the same country and centres in the same city. This study definitively establishes that the prevalence of those diseases can be very high in non-affluent centres with low socioeconomic conditions. The large variability also suggests a crucial role of local environment characteristics to determine the differences in prevalence between one place and another. Thus, ISAAC Phase Three has provided a large body of epidemiological information on asthma, rhinoconjunctivitis and eczema in childhood from contrasting environments which is expected to yield new clues about the aetiology of those conditions and reasons for their marked global variability. © 2012 SEICAP.